Prevalence and factors associated with mortality in fets and newborns with diagnosis of gastroschisis (Research, Society and Development, 2022)
Objective: To analyze the prevalence of mortality and the possible factors associated with this outcome in fetuses and newborns diagnosed with gastroschisis.Methods: This is a cross-sectional and retrospective study with data from neonates born with simple and complex gastroschisis. The outcome variable was mortality (yes/no) from gastroschisis. Independent variables included maternal and neonatal characteristics in fetuses and newborns diagnosed with gastroschisis. The variables were analyzed using multiple Poisson regression. Results: The prevalence of mortality in neonates with gastroschisis was 30.23%. Complex gastroschisis (p=0.002), not performing surgery to close the gastroschisis (p=0.000), performing five surgeries (p=0.000), performing surgery after the second day of birth (p=0.000), were the most important factors associated with increased risk of mortality. Hospitalization in a neonatal ICU (p=0.000) was associated, indicating a protective factor for neonatal mortality. Conclusions: There was a high prevalence of mortality in neonates with gastroschisis. The associated factors highlight the importance of early diagnosis of complex gastroschisis, as well as the early performance of surgery to close the gastroschisis.